Insecticidal Toxicity of Yersinia frederiksenii Involves the Novel Enterotoxin YacT - Springer, Katharina; Sänger, Philipp-Albert; Moritz, Christian; Felsl, Angela; Rattei, Thomas; Fuchs, Thilo M. (Frontiers in Cellular and Infection Microbiology, 2018)
The genus Yersinia comprises 19 species of which three are known as human and animal pathogens. Some species display toxicity toward invertebrates using the so-called toxin complex (TC) and/or determinants that are not yet known. Recent studies showed a remarkable variability of insecticidal activities when representatives of different Yersinia species (spp.) were subcutaneously injected into the greater wax moth, Galleria mellonella. Here, we demonstrate that Y. intermedia and Y. frederiksenii are highly toxic to this insect. A member of Y. Enterocolitica phylogroup 1B killed G. mellonella larvae with injection doses of approximately 38 cells only, thus resembling the insecticidal activity of Photorhabdus luminescens. The pathogenicity Yersinia spp. displays toward the larvae was higher at 15°C than at 30°C and independent of the TC. However, upon subtraction of all genes of the low-pathogenic Y. enterocolitica strain W22703 from the genomes of Y. intermedia and Y. frederiksenii, we identified a set of genes that may be responsible for the toxicity of these two species. Indeed, a mutant of Y. frederiksenii lacking yacT, a gene that encodes a protein similar to the heat-stable cytotonic enterotoxin (Ast) of Aeromonas hydrophila, exhibited a reduced pathogenicity toward G. mellonella larvae and altered the morphology of hemocytes. The data suggests that the repertoire of virulence determinants present in environmental Yersinia species remains to be elucidated.